Anaphylactic Shock Associated with Scratch Testing - Ariyanto Harsono; Muhammad Faizi (Indonesian Pediatric Society, 1996)
A 10-year old boy with bronchial asthma referred to allergy clinic for allergy work-up. He complained of abdominal pain and blurred vision 20-rmnutes after undergoing allergy skin scratch test. Physical examination showed clammy and cyanoÂtic extremities, and hypotension. The skin test result showed positive rection for house dust, mite, and shrimp. Based on these findings the diagnosis of anaphylaxis associÂated with scratch test was made. The suggested offending extract was shrimp with possible interference of the other two extracts. Epinephnne 0.3 subcutaneously was initiated. The first dose gave a disappointing result, and then followed by the second dose which gave better result; dexamethasone was also administered. The eosinophilia, positive specific Ig E to shnmp, house dust and mite as indicated by RAST justify the atopic status of the patient. The management of the main disease consisted of house dust control, elimination diet, and symptomatic treatment were commenced.